THE USE OF INQUIRY-BASED LEARNING MODELS TO DEVELOP STUDENTS' CRITICAL THINKING SKILLS IN SOLVING CONTEXTUAL MATHEMATICS PROBLEMS - Gombo, Mikaus (Universitas Nias Raya, 2025)
This study aims to investigate the impact of using the inquiry-based learning model on students' critical thinking skills in solving contextual mathematics problems. The inquiry-based learning model allows students to actively engage in the learning process through exploration, analysis, and problem-solving related to real-life situations. This research uses an experimental design with an experimental group treated with inquiry-based learning and a control group using conventional learning methods. Data were collected through a critical thinking skills test administered before and after the learning process (pre-test and post-test). The analysis results show that the experimental group experienced a significant improvement in critical thinking skills compared to the control group. Inquiry-based learning encourages students to develop critical thinking skills in solving contextual mathematics problems, as well as enhances active student involvement and motivation in the learning process. This study recommends that the inquiry-based learning model be applied more widely in mathematics education to improve students' critical thinking skills.